NEIM-07 DIFFERENTIAL DIAGNOSIS OF TUMOR RECURRENCE AND RADIATION NECROSIS AFTER STEREOTACTIC RADIOTHERAPY FOR BRAIN METASTASES WITH 320-ROW ADCT PERFUSION IMAGE AND T1/T2 MATCH: RADIOLOGICAL AND PATHOLOGICAL ANALYSIS. (5th August 2022) - Mitsuya, Koichi; Deguchi, Shoichi; Ito, Shohei; Asakura, Koiku; Nakashima, Kazuaki; Oishi, Takuma; Sugino, Takashi; Hayashi, Nakamasa
Abstract: BACKGROUND AND PURPOSE: Radiation necrosis occurs from 6 months to several years following stereotactic irradiation (STI) for brain metastases when tumor recurrences are also most likely. Conventional MR imaging does not provide sufficient information to differentiate between radiation necrosis and tumor recurrence. Methionine-PET, FDG-PET and MR spectroscopy sometimes lead to false positive findings. We applied 320-row area detector CT perfusion imaging for the differentiation because it shows vascularity of lesions in the whole brain. MR T1/T2 match sign also evaluate because it is convenient diagnostic method. METHOD: Between October 2006 and September 2021, 48 lesions enlarged in 46 patients 3 to 122 months (median: 11 months) after STI. Differential diagnosis was performed with CT perfusion imaging and MR T1/T2 match sign. To calculate the regional cerebral blood volume (rCBV), the regions of interest (ROIs) were located in the enhanced areas. The lesions progressively increased in size or became symptomatic were resected and diagnosed by pathological examination. RESULTS: Mean age was 63 years, and 60% were male. Primary were lung 31, breast 9, kidney 3, colon 2, melanoma 2, and uterus 1. Mean time to progression from STI was 11 months (range; 3-122). Pathological diagnosis revealed 38 lesions (79%) had tumor recurrence, and 10 (21%) had radiation necrosis. A cut off value rCBV of greater than 3.0 analyzed by ROC curve provided the best sensitivity and specificity for identifying recurrent metastatic tumors, at 89% and 100%, respectively. T1/T2 match sign was provided sensitivity and specificity for identifying recurrent tumors, at 84% and 90%, respectively. To estimate intralesional pathological heterogeneity, contradistinction of CBV map and T1/T2 match sign is useful for the choice of intraoperative maneuver. CONCLUSION: Perfusion CT imaging and T1/T2 match sign demonstrated reliable methods for differentiating tumor recurrence from radiation necrosis after STI.